Cisza i milczenie w przepowiadaniu słowa Bożego - Pawiński, Sławomir (Studia Pastoralne, 2026)
Analysis of both biblical and liturgical texts leads to a conclusion that silence and quietness are a direct context of revelation of the Word of God, both in the HolyScripture and liturgy. Through silence and quietness God prepares a man for listening and contemplation of the Word of God and the best example of this situation is Mary. Gospel is born in silence of Nazareth, Bethlehem and Golgotha. It is silence and quietness that enwraps Resurrection. Silence and quietness are a part of Gospel and therefore are also a part of preaching. Jesus’ silence in his death on the cross and in his resurrection confirms in a mysterious way Christ’s silence in the sacraments, especially in the Eucharist. Silent presence of God receives now a new sacramental meaning which is exhibited in liturgy. We can enumerate four functions of silence in liturgy: reflexive (providing awareness), meditative, interiorising (inward-directed) and adorative. In preaching these are mainly reflexive and meditative functions that play an important role. Silence and quietness in preaching are signs of a liturgical communication between God and man. In this pattern a vital role is performed by a celebrant and a preacher who introduces, interprets and co-creates „moments of silence” in the Holy Spirit. Silence is a condition of a man’s openness to listening to the Word of God and his silence is a response to the received Word. This liturgical silence is a dimension for the actions of the Holy Spirit, also during reading of the Word of God. A preacher can create „moments of silence” through usage of a logical and psychological pause, rhetorical questions or a prayerful ending of a sermon that does not necessarily have to end with the word „amen” but “a moment of silence” in the Holy Spirit.